Internal audit in self-government entities in Poland. A theoretical and empirical approach - Ćwieląg, Krzysztof (Audyt wewnętrzny w jednostkach samorządu terytorialnego w Polsce. Podejście teoretyczne i empiryczne, 2011)
In the article there has been described an instrument of the internal audit, premise for its introduction, its purpose, the scope and place in the sector of the public finance, with special consideration for the requirements and procedure of the internal audit execution in the self-government entities in Poland. On the basis of conducted examinations, there were made some analysis of the internal audit operation in the self-government sector, with its most important elements taken into account. Based on the findings, a number of final conclusions have been formulated
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 11-32
Keywords: self-government entities; internal audit; organization; tasks